The Happiness of European Tourists (HoET) in Bali: Tourism Services and Happiness Types - Ariana, Nyoman; Putra, Agus Muriawan; Sukana, Made; Panca P, Wayan Agung (E-Journal of Tourism; Volume 10 Number 1 (March 2023), 2023)
European tourists are the primary market of Bali. Therefore, tourism stakeholders consider them as the leading market segment for tourism business and marketing. The main objective of the local tourism industry, when providing services and hospitality, is to generate happiness for European tourists. Based on this background, this research aims to identify the characteristics and types of happiness experiences of European tourists to choose tourism services in Bali. Data are collected through structured interviews, observation, and documentation studies. Respondents consist of 100 European tourists who visited Bali. They are determined by the non-probability sampling method. Data are analyzed by Nvivo 12, statistics, and described qualitatively. The results of the study show that the characteristics of European tourists are dominated by the age of 15-30 years old, female, undergraduate, not married, employee of a private company, to visit colleagues, travel with a friend or spouse, independent travelers, first-time visit, and length of stay of 14 days. The category known as ‘Happiness of European Tourists (HoET)’ in Bali. They are taking various tourism services, including accommodation, dining at restaurants, tours and travel, transportation, local tour guides, tourist attractions, and tourism infrastructure. These aspects are typically classified within the domain of ‘happy’. Upon analyzing the feedback on tourism services, it becomes evident that restaurant services bring the highest level of happiness to European tourists visiting Bali. This finding closely aligns with the tourist response to the accommodation services, which also ‘very happy’. In addition, the empirical research shows that culinary experiences and lodging services hold paramount delight for European tourists during their travels in Bali.